2020
DOI: 10.1108/ir-02-2020-0039
|View full text |Cite
|
Sign up to set email alerts
|

Technology jump in the industry: human–robot cooperation in production

Abstract: Purpose Recent years have seen a technological change, Industry 4.0, in the manufacturing industry. Human–robot cooperation, a new application, is increasing and facilitating collaboration without fences, cages or any kind of separation. The purpose of the paper is to review mainstream academic publications to evaluate the current status of human–robot cooperation and identify potential areas of further re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 109 publications
0
31
0
Order By: Relevance
“…We can define the percentage of time saving or productivity gain in assembly process p by Equation (6). It arises from a reduction in the cycle time of production t c (min) in the assembly process with a cobot and the annual volume of production V, where D is the yearly number of working days, and H is the number of hours per shift.…”
Section: Methodology 21 Differential Cost Model Of Assembly With Collaborative Robotsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can define the percentage of time saving or productivity gain in assembly process p by Equation (6). It arises from a reduction in the cycle time of production t c (min) in the assembly process with a cobot and the annual volume of production V, where D is the yearly number of working days, and H is the number of hours per shift.…”
Section: Methodology 21 Differential Cost Model Of Assembly With Collaborative Robotsmentioning
confidence: 99%
“…This standard defines five main characteristics for all cobots that are the basis of their differences with industrial robots: providing a visual indicator when the robot is operating in cooperation with a human; providing a controlled stop; allowing the operator the possibility of performing manual guidance without the need to deactivate servomotors; supervision of speed and safety distance; and the limitation of power and force by inherent design or control [4]. Collaborative robotics research can be tracked through recent reviews on the topic [5,6], laboratory studies [7,8] or the real field applications that can be found in an increasing number by examining the literature [9][10][11]. Globalization of manufacturing requires considering cobot implementation in several facets for sustainable integration.…”
Section: Introductionmentioning
confidence: 99%
“…For example, human-robot proximity is directly related to organizational safety and health (Zacharaki et al, 2020). A lack of confidence in sensory systems for physical contact also causes concerns about working with robots (Dobra & Dhir, 2020). Another issue is maintaining confidentiality of the data obtained from robots' sensory functions and machine learning (Fletcherd & Webb, 2017).…”
Section: Attributes Related To Contactmentioning
confidence: 99%
“…Various aspects of financing business cooperation have been studied in numerous scholarly papers (Bolgova 2017;Guseva et al 2019;Medentseva 2017;Tarakanov et al 2020). Digital cooperation, as a special form of inter-enterprise collaboration, is a subject of the works of several Russian and foreign scholars (Dobra and Dhir 2020;Huang et al 2020;Kim et al 2020;Lee et al 2020).…”
Section: Literature Reviewmentioning
confidence: 99%